Adding a Structural Context to the Deprotometalation and Trans‐Metal Trapping Chemistry of Phenyl‐Substituted Benzotriazole. Issue 42 (21st September 2015) - Fuentes, M. Ángeles; Kennedy, Alan R.; Mulvey, Robert E.; Parkinson, John A.; Rantanen, Toni; Robertson, Stuart D.; Snieckus, Victor
Abstract Organometallic bases are becoming increasingly complex, because mixing components can lead to bases superior to single‐component bases. To better understand this superiority, it is useful to study metalated intermediate structures prior to quenching. This study is on 1‐phenyl‐1H‐benzotriazole, which was previously deprotonated by an in situ ZnCl2⋅TMEDA/LiTMP (TMEDA=N, N, N′, N′‐tetramethylethylenediamine; TMP=2, 2, 6, 6‐tetramethylpiperidide) mixture and then iodinated. Herein, reaction with LiTMP exposes the deficiency of the single‐component base as the crystalline product obtained was [4‐R‐1‐(2‐lithiophenyl)‐1H‐benzotriazole⋅3THF2], [R=2‐C6H4(Ph)NLi], in which ring opening of benzotriazole and N2 extrusion had occurred. Supporting lithiation by adding iBu2Al(TMP) induces trans‐metal trapping, in which CLi bonds transform into CAl bonds to stabilise the metalated intermediate. X‐ray diffraction studies revealed homodimeric [(4‐R′‐1‐phenyl‐1H‐benzotriazole)2], [R′=(iBu)2Al(μ‐TMP)Li], and its heterodimeric isomer [(4‐R′‐1‐phenyl‐1H‐benzotriazole)2‐R′‐1‐phenyl‐1H‐benzotriazole], whose structure and slow conformational dynamics were probed by solution NMR spectroscopy.